Culture-Specific Items (CSIs) Categories and Translation Procedures of Wang Sinawang Short Movie - Zahra, Firda Safitri El; Indhiarti, Tantri Refa (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
Translating culture-specific items is not easy because it requires knowledge and understanding of a particular culture related to the word. Despite many studies that have been conducted related to translation procedures of culture-specific items (CSIs), there is still a lack in the literature, particularly the procedures in the Javanese to English translations of CSIs in films and short movies. This study used CSIs classification and translation procedures based on Newmark’s (1988). The object of this study was Wang Sinawang, a Javanese short movie which was produced by Dinas Perpustakaan dan Arsip Daerah D.I Yogyakarta and was released on its YouTube channel. This research attempts to find the types and the dominant used procedure that was used by the subtitler of Wang Sinawang short movie to translate the culture-specific items. This study employed a qualitative descriptive methodology. The result revealed that the most CSIs that appeared in the short movie was “Material Culture” which includes foods, clothes, houses and towns, and transportation, while the least CSIs appeared was “Social Culture” which includes work and leisure. The Most used procedure was “Recognized Translation” while the least used procedure was “Naturalization” and “Descriptive Equivalent”. The implication of this study is discussed.